PENINGKATAN KEMAMPUAN PENALARAN MATA UANG SISWA TUNAGRAHITA PRAKTIK JUAL BELI PADA PEMBELAJARAN VOKASIONAL TATABOGA BAGI PESERTA DIDIK - Eni Sulistiowati (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2014)
Learning mathematics is conventionally given , resulting in mental retardation difficulties many students apply in everyday life . Starting from the problem of reasoning researchers suspect the cause is still lacking due to currency ( 1 ) learning to use a conventional model , ( 2 ) learning too abstract , given the characteristics tungrahita children who have difficulty in cognitive development , ( 3 ) no examples taken from everyday problems - days experienced by the child , so the need for ( 1 ) a more attractive approach , ( 2 ) the learning associated with the state of nature , ( 3 ) learning is taken by everyday problems , ( 4 ) the conversion of textual learning how to be contextual. .Base on the research findings , some suggestions can be put forward : a) during the learning needs of learners tunagrahita innovative and contextual learning , b ) should be adapted to the learning environment and the ability of students to instructional design significantly , c ) at the time of the sale and purchase of learning to use the model , should the teacher must determine the readiness of the students participating in learning , motivate students and not always bored to membelajarkan and gives stock purchase science , teachers need to give rewards to students who successfully perform independently.Berawal dari masalah tersebut peneliti menduga penyebab penalaran mata uang masih kurang dikarenakan (1) pembelajaran menggunakan model yang konvensional, (2) pembelajaran terlalu abstrak, mengingat karakteristik anak tungrahita yang kesulitan dalam perkembangan kognitif, (3) contoh-contoh tidak diambil dari masalah sehari-hari yang dialami anak, sehingga perlu adanya (1) pendekatan yang lebih menarik, (2) pembelajaran dihubungkan dengan keadaan alamiah, (3)pembelajaran di ambil berdasarkan masalah sehari-hari, (4) pengubahan cara belajar tektual menjadi kontekstual. Kesimpulan dengan jual beli dalam pembelajaran vokasional tata boga pada peserta didik tunagrahita dapat meningkatkan penalaran mata uang, hal ini terbukti sesuai dengan indikator penalaran yang disajikan secara lisan maupun tertulis.Kemampuan penalaran yang disajikan secara lisan mulai dari menyebutkan, menunjukkan, membedakan, dan asal mata uang. Melalui jual beli dalam pembelajaran vokasional tata boga pada peserta didik tunagrahita dapat terasa lebih bermakna dan sebagai bekal peserta didik untuk menunjang kehidupan sehari-hari dimasyarakat.